WHERE WILL THE EURO-CRISIS TAKE US TO: GERMANY'S THIRD ATTEMPT?. (1st April 2012) - Unknown
Abstract : The volume of global financial transactions has grown faster than the global GDP since 1990. Imperialism leads to ever deeper crises. The financial, banking, and Euro-crisis is a crisis of state monopoly capitalism. Lower wages and deeper social cuts have been the base for higher accumulation in the FRG. German imperialism as the main power within the EU uses the EU and the Euro-crisis as a vehicle to become a world power again.